2017
DOI: 10.1097/igc.0000000000001035
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Radiation Treatment Compliance for Women With Cervical Cancer in a Safety Net Health System

Abstract: Younger patients, those with psychiatric illness, and those with insurance define a group that is more likely to be noncompliant with treatment and hence may require up-front intervention to improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Younger patients, previously associated with more treatment breaks during radiation delivery ( Echeverria et al, 2017 ), were found to also have a higher chance of early interruption of post-treatment surveillance. Other socio-demographic factors (higher number of pregnancies and greater distance from the patient’s home to the community cancer cancer) also negatively affected the compliance.…”
Section: Discussionmentioning
confidence: 95%
“…Younger patients, previously associated with more treatment breaks during radiation delivery ( Echeverria et al, 2017 ), were found to also have a higher chance of early interruption of post-treatment surveillance. Other socio-demographic factors (higher number of pregnancies and greater distance from the patient’s home to the community cancer cancer) also negatively affected the compliance.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have looked at treatment compliance as an outcome of interest either for a particular disease or a combination of diseases [ 15 , 16 , 23 ]. However, as far as we are aware, these studies have focused their analysis on a univariate association of the available variables with the endpoint treatment compliance in (elderly) cancer patients.…”
Section: Introductionmentioning
confidence: 99%